The Association between the Pulmonary Arterial Obstruction Index and Atrial Size in Patients with Acute Pulmonary Embolism. (2nd June 2019) - Faghihi Langroudi, Taraneh; Sheikh, Maryam; Naderian, Mohammadreza; Sanei Taheri, Morteza; Ashraf-ganjouei, Amir; Khaheshi, Isa
Abstract : Purpose . Pulmonary embolism (PE) is a common and potentially fatal form of venous thromboembolism. The aim of this study is to investigate the association between the pulmonary arterial obstruction index and atrial size in patients with acute pulmonary embolism. Basic Procedure . The study consisted of 86 patients with clinical symptoms of PE. Out of 86 individuals, 50 patients were diagnosed with PE and considered as the patient group. The others were considered as the control group. All patients were scanned by a multidetector CT scanner. Using the radiology workstation, an expert radiologist calculated the left atrium (LA) and right atrium (RA) areas from planimetric measurements obtained from free-hand delineation of the atrial boarders using an electronic pen. Quantitative volumetric measurements of LA and RA were obtained from original axial images. Main Findings . There were 25 males and 25 females with PE, who had a mean age of 58 years. There was not a significant difference in the positive history of diabetes mellitus, hypertension, asthma, chronic obstructive pulmonary diseases, ischemic heart disease, and smoking between patients and control group. There was a significant negative correlation between almost all LA measurements and the PAOI. RA area and volume had the highest area under the curves for recognizing larger clot burden. Principal Conclusions . A higher clot load is associated with a smaller LA size and increased RA/LA ratios, measured with CTPA. Atrial measurements are correlated with POAI, and they could be used as sensitive parameters in predicting heart failure in patients with PE.